Surasundari on the west wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Surasundari (celestial damsel) on the west wall of the garbhagriha (sanctum sanctorum) of Shiva Temple 1 is carved next to the main central niche. The surasundari stands with grace, her body exuding vitality as she grasps a flower stem in one hand and the edge of a scarf in the other.